The Dimensions of the Prophetic Discourse in the 40 Hadiths Nawawi - Al-Zuhayre, Mahmoud Hussein Ahmad (Journal of Social Sciences (COES&RJ-JSS), 2021)
This paper aims at exploring the rhetoric of the prophetic discourse in the Hadiths collected by Al-Nawawi. It is composed of four aspects. Firstly, public discourse by using thewordswho and all, or what pertains to a specific incident for a person whose name was not assigned for polite purposes, so that the speech is directed to any recipient or Muslim over time, focusing on the event not on the person and associating actions with their past and present times.Therefore, the rhetoric was expressed as a result of arranging the words, employing them and their beauty in harmony with their context and location. Secondly, the command and prohibition discourse of the individual and the group according to the purpose of the discourse and its rhetoric with the beauty that was brought about in the style and verbal ornaments associated with the status of the recipient. For example, "O, Sons of Adam", "O Young boy", and "O My Servants " in the Qudsi Hadith, employing the method of urging, "May I..?". Such wordings were crowned by the aspect of the wording texts, briefly and shortly in terms. However, it included great meanings and benefits with beautiful phrases and eloquent style, implying social, educational and global dimensions that have their impact on the recipient. These phrases have had their echo in societies and assemblies, such as, "(The value of) an action depends on the intention behind it" and ".. And he who is slow-paced in doing good deeds, his (high) lineage does not make him go ahead.", that have made them general rules and a method of life to be followed.